APLIKASI SISTEM PAKAR PENENTU BIDANG STUDI DITINGKAT PERGURUAN TINGGI BERBASIS WEB - Terttiaavini Terttiaavini; Sumi amariena Hamim; Suzan Agustri (Jurnal Informatika Global)
Reason one choose a field of study is that we often hear when the students are studying. This can occur because most students choose majors based on the strong influence of the environment, such as a friend or a parent. By the time these students realize that their chosen field of study is not in accordance with the potential of the talent they have, timbulah regrets later on. If a case of choosing this field of study continues, it will affect the learning achievement of the students themselves. Effect of talent with accomplishment is strong. But it was not easy to know one's talent. To find potential talent necessary psychological test and consultation with a psychologist who will not be cheap. Therefore timbulah idea to build an expert system that can detect potential talent that can provide an alternative appropriate field of study based on the potential talents. Detecting potential talent is done by psychometric analysis. Psychometric analysis is used as a tool to determine a person's field of study. Through quantitative analysis will be done the preparation of test item is valid and reliable. The results of the analysis of an expert system, same / approach with the ideas of a specialist / psychologist. The model used to build the expert system is a decision tree model (decesion tree) using algorithms C.4.5. The expert system is implemented through a web-based application. Web-based expert system can be easily accessible, anywhere and anytime, and thus will be more efficient utilization and dissemination. With this application, is expected to help potential mahsiswa in determining the appropriate field of study based on the potential of the talent they have.Key word : Expert systems, Decision tree model, Psychometric analysis, Web applications